Mapping Caregivers’ Health Assets. A self-care project using Salutogenesis and Mindfulness: Mapping Cargivers’ Health Assets - Alpuente, Alejandro Camacho; Cintas, Francisca Anaya; Foà, Chiara; Cosentino, Chiara (Acta Biomedica Atenei Parmensis, 2018)
Background: Thousands of caregivers around the world take care of impaired people, with negative repercussions on their physical, psychological, social and economic resources. The need to promote caregivers’ wellbeing is internationally recognized, thus reducing health inequalities. Mindfulness is a powerful tool, directly related to the reduction of stress, able to increase skills and attitudes promoting well-being. The basis of this project of community development based on active health, is the self-care achieved through mindfulness. Aims: The overall aim of this project is to improve the caregivers’ health and quality of life through community mapping strategies and mindfulness. Methods: According to the salutogenic model, and to the model of community development based on active health (ABCD) we will create a map of the caregivers’ internal and external health assets. The project will have a participatory action research methodology, and it will go throygh five different phases, with mindfulness as a central tool. Results: At the end of the project, results will be analyzed referring to structures, processes and objective and subjective outcomes. Conclusions: At the end of the project, we will evaluate if the Salutogenic ABCD methodology along with Mindfulness, will be able to reduce health inequalities improving caregivers’ wellbeing.